Discarded Human Thymus Is a Novel Source of Stable and Long‐Lived Therapeutic Regulatory T Cells. Issue 1 (28th September 2015) - Dijke, I. E.; Hoeppli, R. E.; Ellis, T.; Pearcey, J.; Huang, Q.; McMurchy, A. N.; Boer, K.; Peeters, A. M. A.; Aubert, G.; Larsen, I.; Ross, D. B.; Rebeyka, I.; et al.
Abstract: Regulatory T cell (Treg)–based therapy is a promising approach to treat many immune‐mediated disorders such as autoimmune diseases, organ transplant rejection, and graft‐versus‐host disease (GVHD). Challenges to successful clinical implementation of adoptive Treg therapy include difficulties isolating homogeneous cell populations and developing expansion protocols that result in adequate numbers of cells that remain stable, even under inflammatory conditions. We investigated the potential of discarded human thymuses, routinely removed during pediatric cardiac surgery, to be used as a novel source of therapeutic Tregs. Here, we show that large numbers of FOXP3 + Tregs can be isolated and expanded from a single thymus. Expanded thymic Tregs had stable FOXP3 expression and long telomeres, and suppressed proliferation and cytokine production of activated allogeneic T cells in vitro . Moreover, expanded thymic Tregs delayed development of xenogeneic GVHD in vivo more effectively than expanded Tregs isolated based on CD25 expression from peripheral blood. Importantly, in contrast to expanded blood Tregs, expanded thymic Tregs remained stable under inflammatory conditions. Our results demonstrate that discarded pediatric thymuses are an excellent source of therapeutic Tregs, having the potential to overcome limitations currently hindering the use of Tregs derived from peripheral or cord blood. Abstract : Discarded pediatric thymus is a source of therapeutic CD4 + CD25 + FOXP3 + regulatory T cells that are more potent, stable and long‐lived than CD4 + CD25 + FOXP3 + regulatory T cells isolated from peripheral blood.